Differential Expression Patterns of Lynx Proteins and Involvement of Lynx1 in Prepulse Inhibition - Sherafat, Yasmine; Chen, Edison; Lallai, Valeria; Bautista, Malia; Fowler, James P.; Chen, Yen-Chu; Miwa, Julie; Fowler, Christie D. (Frontiers in Behavioral Neuroscience, 2021)
Negative allosteric modulators, such as lynx1 and lynx2, directly interact with nicotinic acetylcholine receptors. The nicotinic acetylcholine receptors are integral to cholinergic signaling in the brain and have been shown to mediate different aspects of cognitive function. Given the interaction between lynx proteins and these receptors, we examined whether these endogenous negative allosteric modulators are involved in cognitive behaviors associated with cholinergic function. We found both cell-specific and overlapping expression patterns of lynx1 and lynx2 mRNA in brain regions associated with cognition, learning, memory, and sensorimotor processing, including the prefrontal cortex, cingulate cortex, septum, hippocampus, amygdala, striatum, and pontine nuclei. Since lynx proteins are thought to play a role in conditioned associations and given the expression patterns across brain regions, we first assessed whether lynx knockout mice would differ in a cognitive flexibility task. We found no deficits in reversal learning in either the lynx1-/- or lynx2-/- knockout mice. Thereafter, sensorimotor gating was examined with the prepulse inhibition (PPI) assessment. Interestingly, we found that both male and female lynx1-/- mice exhibited a deficit in the PPI behavioral response. Given the comparable expression of lynx2 in regions involved in sensorimotor gating, we then examined whether removal of the lynx2 protein would lead to similar behavioral effects. Unexpectedly, we found that while male lynx2-/- mice exhibited a decrease in the baseline startle response, no differences were found in sensorimotor gating for either male or female lynx2-/- mice. Taken together, these studies provide insight into the expression patterns of lynx1 and lynx2 across multiple brain regions and illustrate the modulatory effects of the lynx1 in sensorimotor gating.